Intermittent High-Dose Vitamin D3 Administration in Neonates with Multiple Comorbidities and Vitamin D Insufficiency - Catalin Cirstoveanu; Iulia Ionita; Carmina Georgescu; Carmen Heriseanu; Corina Maria Vasile; Mihaela Bizubac (MDPI AG, 2024)
Background: Neonates have an increased risk of vitamin D insufficiency due to the inadequate supplementation of mothers and infants after birth. Insufficiency of vitamin D is frequently detected in critically ill patients and is associated with disease severity and mortality. There is yet to be a consensus on the appropriate regimen of vitamin D3 supplementation in high-risk infants. Aim: The main objectives of this study were to determine the prevalence of vitamin D insufficiency in neonates with severe comorbidities and to evaluate whether high-dose vitamin D3 oral administration leads to normal plasmatic concentrations without side effects. Methods: The current study was a randomized, prospective trial of 150 patients admitted to the Neonatal Intensive Care Unit (NICU) at Maria Sklodowska Curie Emergency Children's Hospital in Bucharest. Patients were divided into three subgroups based on the chronological order of their admission date. Each subgroup received a different pharmaceutical product of vitamin D3. We administered a dosage of 10,000 IU/kg of vitamin D3 orally in three steps, as follows: at admission, one week after admission, and one month from the first administration, targeting a serum 25-hydroxyvitamin D concentration of at least 40 ng/mL. Results: Most neonates (68%) achieved an optimum vitamin D level after one month, even though only 15% of patients had an optimum concentration at admission. After the first high dose of vitamin D3, there was a 27% increase in the mean vitamin D plasmatic level compared to admission levels. However, after one month, the concentrations decreased in all subgroups due to the gap of three weeks between the last two administrations. Conclusions: An intermittent, weekly high-dose vitamin D3 oral administration leads to a steadier increase and normalization of vitamin D concentration in most critically ill neonates. However, high-dose vitamin D3 administered orally after three weeks decreases vitamin D levels in this high-risk population.